Produk, Kenyamanan, Harga Dan Lokasi Terhadap Keputusan Pembelian Konsumen - Yosef Moan Banda; Sayful Amrin; Siti Widya Rana (Program Studi Pendidikan Ekonomi, Universitas Flores, 2022)
This paper discusses the influence of products, services, locations and prices on consumer purchasing decisions of Roxy Supermarkets, using data collection techniques: observation, questionnaires. The collected data were analyzed using the moment product correlation coefficient. Based on the data analysis and discussion, it proves the significant value (sig) of the anova output because the Sig value is 0.000 <0.05, according to the decision making in the F test it is concluded that the hypothesis is accepted or X1, X2, X3, and X4 simultaneously affect Y. while the comparison it is known that the calculated F value with F table is 35.395 > F table 3.06, it is concluded that the hypothesis is accepted or in other words X1, X2, X3, and X4 simultaneously affect Y. (2) R-Square value which is 0.756 shows that the proportion of influence of variables X1, X2, X3, and X4 on variable Y is 75.6%, meaning that products, services, locations and prices at Roxy Supermarkets have a proportion of influence on purchasing decisions of 75.6% while the remaining 24.4% (100%) -75.6%) is influenced by other variables that are not in the model.